2020
DOI: 10.1177/1179548420913281
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Physician Perspectives on Systemic Sclerosis–Associated Interstitial Lung Disease

Abstract: Systemic sclerosis–associated interstitial lung disease is challenging to diagnose and treat. Patients and physicians can perceive the disease differently and have different views on its management. Communication issues between them can lead to suboptimal disease management. Despite a clear need for improvement in the speed and accuracy of the diagnostic workup, the heterogeneity of clinical symptoms renders the process long and challenging. When considering treatment options, physicians may be more focused on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…These findings are in line with patient perceptions about essential outcomes of treatment in SSc and other rheumatic diseases, which showed that quality of life and daily functioning were highly prioritized. 16,17 There were three rounds and a live online meeting needed to reach agreement on the items, which reflects the different views of individual patients on this subject. Furthermore, no agreement was reached on items about infertility and disease relapse, which are relatively common adverse events for CYC and SCT with considerable impact on quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are in line with patient perceptions about essential outcomes of treatment in SSc and other rheumatic diseases, which showed that quality of life and daily functioning were highly prioritized. 16,17 There were three rounds and a live online meeting needed to reach agreement on the items, which reflects the different views of individual patients on this subject. Furthermore, no agreement was reached on items about infertility and disease relapse, which are relatively common adverse events for CYC and SCT with considerable impact on quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with patient perceptions about essential outcomes of treatment in SSc and other rheumatic diseases, which showed that quality of life and daily functioning were highly prioritized. 16 , 17 …”
Section: Discussionmentioning
confidence: 99%
“…Patient education is a valuable component of disease management, and may enhance shared decision making and communication, increase concordance with treatment, reduce anxiety, and help patients to feel more in control [ 37 ]. Educated patients are more likely to use healthcare services in a responsible way and obtain higher benefits from treatment [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, educating patients is more challenging than educating healthcare professionals, as the patients’ own health issues, diverse backgrounds, and language can create significant barriers [ 42 ]. Furthermore, the complex aetiology and heterogeneity of some diseases make it even more difficult to provide accurate, tailored disease education to patients [ 37 , 43 ]. A personalized approach, taking into account the individual’s goals, personal preferences, cultural beliefs and lifestyle is needed [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…To secure implementation of these recommendations in daily clinical practice, it is important to identify remaining unmet needs in all phases of the patient journey [ 9–12 ]. These include pre-diagnostic, diagnostic and post-diagnostic phases, as experienced by healthcare providers (HCPs) and patients themselves [ 13 ]. It is well-known from other life-threatening diseases that actively involving patients in therapeutic decision-making is crucial for self-management and compliance [ 14 ].…”
Section: Introductionmentioning
confidence: 99%